GE_GERICHTE P/20677/2018 vom 2. April 2019 - GE Cour de justice (2019)
PRINCIPE DE LA CÉLÉRITÉ;ESCROQUERIE;ABUS DE CONFIANCE;CONCURRENCE DÉLOYALE | cpp.29; cpp.310; cp.146; cp.138; LCD.23; LCD.5; Cst.29